KONTRIBUSI PENGUASAAN UNSUR INSTRINSIK TERHADAP KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS IX SMP NEGERI 20 PADANG - Azzahra, Fatimah; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research is to description of the following. First, describe the mastery level of instrinsik element of grade IX SMP Negeri 20 Padang. Second, describing the skill level of writing short story students in class IX SMP Negeri 20 Padang. Thirdly, it describes the contribution of Instrinsik element mastery to the short story writing skills of class IX SMP Negeri 20 Padang. This type of research is quantitative using a descriptive method with a correlation approach. The population amounted to 285 people and was spread in nine classrooms. This research sample amounted to 57 people. The research Data is a result of the objective test of multiple-choice for an Instrinsik element mastery test consisting of 42 grains. Student short story writing skills Data is obtained by conducting a performance test. The collected Data is analyzed according to the indicators to get student scores and grades. Based on the results of the study, three sympultants were obtained. First, the skills of short story writing students IX SMP Negeri 20 Padang Panjang in general are on the qualification more than enough with an average value of 72.15.Â Secondly, the mastery of instrinsik element of grade XI SMP Negeri 20 Padang is being qualified more than enough with the average value of 69.76 count. Thirdly, the mastery of language style contributes to the short story writing skills of class IX SMP Negeri 20 Padang by 32.49%, while the rest is influenced by other factors that are not researched in this study.Â Kata Kunci: Kontribusi, Unsur Instrinsik, Menulis Cerita Pendek